Nanoscale electronic devices based on transition metal dichalcogenides. (3rd June 2019) - Zhu, Wenjuan; Low, Tony; Wang, Han; Ye, Peide; Duan, Xiangfeng
Abstract: Two-dimensional (2D) transition metal dichalcogenides (TMDs) have very versatile chemical, electrical and optical properties. In particular, they exhibit rich and highly tunable electronic properties, with a bandgap that spans from semi-metallic up to 2 eV depending on the crystal phase, material composition, number of layers and even external stimulus. This paper provides an overview of the electronic devices and circuits based on 2D TMDs, such as Esaki diodes, resonant tunneling diodes (RTDs), logic and RF transistors, tunneling field-effect transistors (TFETs), static random access memories (SRAMs), dynamic RAM (DRAMs), flash memory, ferroelectric memories, resistitive memories and phase-change memories. We address the basic device principles, the advantages and limitations of these 2D electronic devices, and our perspectives on future developments.